Body Composition Using Air Displacement Plethysmography in Children With Intestinal Failure Receiving Long‐Term Home Parenteral Nutrition. Issue 2 (22nd March 2019) - Neelis, Esther; Kouwenhoven, Stefanie; Olieman, Joanne; Tabbers, Merit; Jonkers, Cora; Wells, Jonathan; Fewtrell, Mary; Wijnen, René; Rings, Edmond; de Koning, Barbara; Hulst, Jessie
Abstract: Background: Children with intestinal failure (IF) are at risk of growth failure, but little information about body composition is available. Our aim was to assess body composition using air displacement plethysmography (ADP) and relate it to clinical and growth parameters. Methods: In this prospective descriptive observational 2‐center cohort study, children aged 2–18 years receiving home parenteral nutrition (PN) for ≥6 months underwent ADP measurement. Fat mass index (FMI) and fat‐free mass index (FFMI) standard deviation scores (SDSs) were calculated to normalize for small body size. Results: Twenty‐one out of 22 children, median age 7.4 years, underwent successful ADP measurement after a median PN duration of 5.5 years. They were significantly lighter (median weight for age SDS −0.71, P = 0.004) and shorter (median height for age SDS −1.55, P < 0.001) than the normal population mean; 52% were growing below target height range. They had low FFMI (median SDS −1.53, P < 0.001) and high FMI (median SDS 0.80, P = 0.002). Weight for height and body mass index (BMI) were significantly associated with FFMI and BMI with FMI, but children with the same weight and height showed different body composition. In 13 patients with 1‐year follow‐up, growth and body composition did not change significantly. Conclusion: Children with IF receiving long‐term PN show lower FFM and higher FM than healthy children. Additionally, children with similar routine growth parameters showed different body composition. Further studies should evaluate the effect of a patient‐tailored approach including physical activity and nutrition advice based on body composition.